2005
DOI: 10.1089/jwh.2005.14.339
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fingernails as a Means of Assessing Bone Health: A Pilot Study

Abstract: Bone collagen and nail keratin are two distinct structural proteins, and both require protein sulfation and disulfide bond formation, via cysteine, for structural integrity. A disorder of either process may lead to disordered collagen and keratin synthesis. This is reflected in the structural abnormalities seen in clinical syndromes in which there is either protein deficiency, disorders of sulfur metabolism, or cystathione beta-synthase deficiency. The relationship between nail and bone may exist in a measurab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 9 publications
5
27
0
3
Order By: Relevance
“…There was no significant difference between smokers and non-smokers in serum levels of osteocalcin and CTx. Significantly lower disulphide content of fingernails was again observed in subjects with a history of fracture and this is in agreement with previous studies [20,24]. In comparison to the other methods used in this study the BQT discriminated most accurately between the control and fracture cases (p = 0.003; Table 2).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There was no significant difference between smokers and non-smokers in serum levels of osteocalcin and CTx. Significantly lower disulphide content of fingernails was again observed in subjects with a history of fracture and this is in agreement with previous studies [20,24]. In comparison to the other methods used in this study the BQT discriminated most accurately between the control and fracture cases (p = 0.003; Table 2).…”
Section: Resultssupporting
confidence: 92%
“…Preliminary work by the authors has evaluated the use of Raman spectroscopy to investigate the link between fingernail protein structure (keratin) and bone protein structure (collagen) [20,24,26]. Both proteins require cysteine incorporation and sulphation for structural integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nail material contains calcium phosphate which also occurs in bones, and bone mineral density is lower in females than in males. This explanation would agree with findings of Pillay et al [24] who analyzed the disulfide bond content in fingernails with Raman spectroscopy. They found that osteoporotic patients with reduced bone mineral density had lower disulfide bond content in their nails compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…An Irish study demonstrated that nail testing as such a method is inconclusive but these preliminary findings suggest that changes in bone proteins seen in osteoporosis may be mirrored by changes related to structural proteins [40,41]. …”
Section: Discussionmentioning
confidence: 99%